Bearskin - McLaughlin, James A. (Ecco, an imprint of HarperCollinsPublishers, 2018)
Rice Moore is just beginning to think his troubles are behind him. He<U+2019>s found a job protecting a remote forest preserve in Virginian Appalachia where his main responsibilities include tracking wildlife and refurbishing cabins. It<U+2019>s hard work, and totally solitary<U+2014>perfect to hide away from the Mexican drug cartels he betrayed back in Arizona. But when Rice finds the carcass of a bear killed on the grounds, the quiet solitude he<U+2019>s so desperately sought is suddenly at risk. More bears are killed on the preserve and Rice<U+2019>s obsession with catching the poachers escalates, leading to hostile altercations with the locals and attention from both the law and Rice<U+2019>s employers. Partnering with his predecessor, a scientist who hopes to continue her research on the preserve, Rice puts into motion a plan that could expose the poachers but risks revealing his own whereabouts to the dangerous people he was running from in the first place.